the Effectiveness of Logo Complexity on the Success of Company Brand Awareness - Kurniadi, Terry; Harnoko, Irwan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2024)
In this highly competitive retail landscape, building a very distinctive brand identity is one of the most crucial factors for the growth and success of a certain brand. One essential element of their identity is the logo of the brand, serving as a visual representation of the brand. This study questions: Does the logo design truly have a significant impact on brand awareness? Through examination of existing literature, consumer psychology theories, this journal article investigates the relationship between logo design and the popularity of a company. By focusing on the interplay between visual branding and media following, this research aims to provide valuable insights for marketers, designers, and store owners who seek to utilize logo design as a strategic tool to drive growth in today's very dynamic retail environment.